1-Benzoyl-3,3-bis(propan-2-yl)thiourea - Gunasekaran, N.; Karvembu, R.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent thiourea derivatives comprise the asymmetric unit of the title compound, C(14)H(20)N(2)OS. The major difference between the molecules relates to a twist in the relative orientation of the benzene rings [torsion angles = 4.5 (2) and -19.9 (2)degrees for the two independent molecules]. The thiocarbonyl and carbonyl groups lie to opposite sides of the molecule as there are twists about the central N-S bond [torsion angles = 83.90 (15) and 81.77 (15)degrees]. Supramolecular chains extending parallel to [101] with a stepped topology and mediated by N-H...O hydrogen bonding feature in the crystal structure. C-H...O and C-H...pi interactions are also present.